Analisis Perbedaan Perilaku Online Impulse Buying Gen Z Dan Gen Y Ditinjau Dari Hedonic Shopping Motivation (Survei Pada Pengguna E-Commerce Shopee di Wilayah Kota Tasikmalaya) - Agustin, Laela; Fitriadi, Budhi Wahyu; Yusnita, Rita Tri (Jurnal Bisnis, Manajemen dan Akuntansi, 2024)
This study aims to determine the differences in online impulse buying behavior of gen z and gen y in terms of hedonic shopping motivation in shopee e-commerce users in Tasikmalaya City. The research method used in this research is quantitative research with causality method and survey approach. The population in this study is not known with certainty. The sampling technique in this study is nonprobability sampling with a total sample size of 100 people who are shopee e-commerce users with group divisions, namely 50 gen z people and 50 gen y people. The type of data used is primary data obtained from questionnaires. The data testing techniques used in this study are validity test, reliability test and independent sample t-test and simple linear regression analysis using SPSS version 25. The results of this study indicate that there is no significant difference in Hedonic Shopping Motivation between Gen Z and Gen Y. There is a significant difference in Online Impulse Buying between Gen Z and Gen Y. Hedonic Shopping Motivation has a significant effect on Gen Z's Online Impulse Buying. Hedonic Shopping Motivation has a significant effect on Online Impulse Buying Gen Y.